Uncovering Management Issues in Australian Classrooms Experienced by Non-English Speaking Background Teachers - Afzal, Bushra; Taylor, Peter Charles (Journal of Education and Research, 2016)
Teachers from non-English-speaking background (NESB) constitute an important community of teachers in Australia, especially in Mathematics and Science discipline. During their journey of resuming teaching in Australian schools, they encounter a number of problems, including classroom management issues. Being an NESB teacher I have experienced acute classroom management problems, mostly related to students’ behaviour and have been desperate to know the reality of the issue for other teachers. In this autoethnographic research, I developed a deeper understanding of these problems and possible solutions. I held a series of ’good conversations’ with four NESB teachers from the Indian subcontinent. I represented the conversations in the form of narratives and subsequently subjected them to scholarly interpretive analysis. The study illustrates ways in which these NESB teachers faced severe student behaviour problems, which was a source of deep frustration for them. Major factors contributing towards these problems are cultural differences, language barriers and racism. I have learned from this study that NESB teachers, including myself, could improve class management skills by undertaking behaviour management courses prior to resuming teaching in a seemingly alien culture. Class management skills of NESB teachers can also improve with experience.